Estudio descriptivo de la creatividad en el proceso pedagógico, para desarrollar habilidades cognitivas en los alumnos de segundo año de educación general básica, de la unidad educativa “Angel Polibio Chaves” del cantón San Miguel, provincia Bolívar, estudio realizado durante los meses de diciembre del 2021 a marzo del 2022 - García León, María José (2022)
The research carried out focuses on the descriptive study of creativity in the pedagogical process, to develop cognitive skills in second-year students of Basic General Education of the "Ángel Polibio Chaves" Educational Unit of the San Miguel canton, Bolívar Province, carried out during the months of December 2021 to March 2022, allowing boys and girls to be dynamic, critical, reflective, creative, where they can express their thoughts, feelings, emotions and ideas through creativity, under the intervention and pedagogical mediation of the teacher, who proposes methodological strategies to address verbal, analytical, non-verbal, spatial, analogical, aesthetic, specific operations within the development of cognitive skills. Basic education in times of pandemic focuses on a constant discussion of how to improve virtual teaching processes, since it involves the mediation of new sharing roles for pedagogical monitors in the realization of learning. Developing cognitive skills, through creativity, will make the pedagogical process viable in students. Where, creativity allows students to develop pedagogical autonomy and cognitive will, with freedom to express themselves, be critical-innovative, spontaneous and deciders of self-investigation and self-induction. XI The research was qualitative, the operationalization instrument was the interview and a questionnaire derived from the objects of knowledge addressed in the research problem